A Bibliometric Review of Macroeconomic Stability - Loso Judijanto (Westscience Press, 2026)
This study provides a bibliometric review of macroeconomic stability research, examining the evolution of key themes, influential authors, and emerging trends in the field. Using citation analysis, co-authorship networks, and keyword co-occurrence mapping, the review identifies the core topics in the literature, including financial stability, monetary policy, inflation, and economic growth. The findings reveal a shift from traditional macroeconomic concerns, such as inflation control and fiscal discipline, to more integrated approaches that consider financial system stability, economic development, and sustainability. Furthermore, the study highlights the increasing importance of climate change and global economic interdependence in shaping macroeconomic stability. The analysis underscores the growing complexity of macroeconomic stability research, with interdisciplinary collaboration and the integration of environmental and social concerns playing a key role in future studies. This paper contributes to a better understanding of the dynamic nature of macroeconomic stability and offers insights for future research directions.